Quality Requirements and the Requirements Quality: The indications from Requirements Smells in a Financial Institution Systems - Calazans, Angelica Toffano Seidel; Paldês, Roberto Ávila; Canedo, Edna Dias; Masson, Eloisa Toffano Seidel; Guimarães, Fernando de Albuquerque; Rezende, Kiane Mabel Fialho; Gonçalves, Fábio de Souza; Mariano, Ari Melo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Systems quality requirements are defined by ISO/IEC 25000 series. In specifying these requirements, using Natural Language, it is possible that there are symptoms of low quality, Requirements Smells (RSs). The present work has the objective of confirming and analyzing the presence of Requirements Smells in specifications of quality requirements classified by ISO/IEC 25010. The specifications of 26 systems of a large public financial organization were analyzed. Content analysis and Nvivo software were used and 870 quality requirements were categorized and analyzed. As a result, it was verified that 44% of the analyzed requirements present Requirements Smells which signals the importance of the inspection of the requirements with this bias. It was also identified that the most representative RSs are related to Subjective Language (34.6%), Incomplete Reference (22%) and Non verifiable terms (16%). The RSs less found in the specifications are of the Superlative, Loopholes and Comparative categories.